Growth strategy, entrepreneurial capability and business success of SMEs in Kedah - Ahmad Rafiq, Muda (2018)
The purpose of this research is to investigate the business strategy and performance in Small and Medium-Sized enterprises (SMEs). The research focused on SMEs because of the importance of SMEs in the economy and the high percentage of them in the Malaysian business population. The present research examined the relationship between entrepreneurial capability, growth strategy and SMEs business success. The entrepreneurial capability consisted of entrepreneurial self-efficacy and improvisational behaviour, and growth strategy included product development strategy, market penetration strategy and market development strategy. This research used a survey methodology, then analysed by using a descriptive analysis, correlation and regression analysis. Findings showed that each independent variable had mixed results on SMEs business success. This study contributed to the flow of RBV and provided important contributions for practitioners in developing policies and strategies for business success among SMEs in Malaysia.